Ο στερνός΄ Από τη δεύτερη ελεγεία΄Άλλος από τη δεύτερη ελεγεία - Rilke, Rainer Maria (Μακεδονικές Ημέρες, 1932)
Lyrik
Keywords: Konstantinos Jeorgoulis (Κωνσταντίνος Γεωργούλης) (!); Rainer Maria Rilke